The Archers: an everyday story of old and new media. - Thomas, Lyn (Radio Journal: International Studies in Broadcast & Audio Media, 2009)
This article explores the evolving relationship between the world's oldest radio soap opera — The Archers — and the online spaces around the programme created on the BBC Archers website, particularly the fan cultures that have developed on its messageboards. It considers continuities and changes in listeners' relationships with the experience of radio soap opera which result from participation in these cultures and the availability of the programme online. This article then provides detailed analysis of the nature and functioning of the fan cultures which have colonised the BBC ‘Discuss The Archers’ board, and relates this discussion both to Bourdieu's theories of cultural distinction and to the broader field of fan studies. This article concludes by discussing the struggles for meaning which result from the clash of different versions of fandom online. Reprinted by permission of the publisher.